(untitled) (Sains Humanika, 2021)
This study aims to understand the dynamics of smoking attitudes and behavior in Muhammadiyah residents. This research uses qualitative research methods by using case studies. The three informans are the management of the Regional Leader Major Islamic non Govermental Organization in Indonesia (Pimpinan Daerah Muhammadiyah - PDM) of the Banyumas region and the Muhammadiyah Tobacco Control Center (MTCC) of the Universitas Muhammadiyah Purwokerto, where three participants are smokers of Muhammadiyah residents. The study found four factors that caused Muhammadiyah residents to smoke after the issuance of the prohibited fatwa on smoking, namely the meaning of the fatwa that was still being prepared, subjective, faith that was still weak, and fatwa added more in accordance with medical assistance.